Resolvemos problemas para hallar el termino desconocido de una ecuación - Moreno Cochachi, Herlinda Janeth (2020)
Learning Standard for children who are in the 5th grade in Primary Education in 2019 in which great contributions have been made to the CNEB from the perspective of developing Competences skills of the proposed level and which are expected to be acquired by our students. The topic: "Solving problems to find the unknown term of an equation" it frames its development in the daily situations of students' lives, in which they are challenged to establish relationships between data and unknown values. Students will acquire definitive notions about Equality when finding the unknown terms of an equivalence and its relations of variation between two magnitudes and in turn transforms them into simple equations when working with natural numbers. In the designing of this lesson, the pedagogical and didactic process of the Mathematics area has been taken into account, which through its current pedagogical conception aims to achieve significant learning in students. _x000D_ In the development of the lesson, the strategies that have been used, guide the active and meaningful participation of all students as a means of achieving their learning when developing the practice sheet